TRANSFORMATION OF SOCIO-POLITICAL COMMUNICATION IN THE 2024 REGIONAL ELECTIONS IN SOUTH SULAWESI - Hasruddin Nur; Najamuddin; Hasanudin Kasim (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The 2024 regional elections in South Sulawesi reflect a significant transformation in socio-political communication, marked by the growing dominance of digital media as the primary arena for political engagement. This study investigates the transition from conventional, elite-centered campaign models to digitally networked forms of interaction, and analyzes how candidates strategically construct and disseminate political messages across online platforms. Employing a qualitative design, the research integrates framing theory with multimodal digital discourse analysis to examine campaign materials circulated on major social media platforms during the 2024 electoral period. Data were collected through systematic documentation of textual posts, images, videos, and interactive exchanges between candidates and citizens. The analysis focuses on narrative framing, symbolic representation, and patterns of audience engagement. The findings reveal a clear shift from hierarchical, one-way communication toward more participatory, dialogic, and interactive political exchanges. Candidates increasingly relied on multimodal resources combining text, visuals, audio, and short-form video to craft persuasive narratives, shape public perception, and mobilize voters. In addition, platform algorithms and interactive features reshaped the dynamics of influence between political elites and the electorate. Overall, socio-political communication in the 2024 elections demonstrates a hybrid digital model that redefines campaign strategies, public deliberation, and democratic participation at the regional level.